Policy of living donors : a study of quality of life of kidney donors in Malaysia / Noorzalikha binti Kamar - Kamar, Noorzalikha (2013)
According to the 2009 WHO Guiding Principles on Human Organ Transplantation Report of the Regional Meeting, Malaysia is still absent of living kidney donor registry up to 2012. Among the 15,399 patients on the waiting list of organ transplantation, 99 percent of them are kidney patients and thus the entire donation related promotions should be focused on kidney. Living donors are important source of the increasing hope of organ donations since the increase of deceased organ donations solely unavailable. But while living donation rates are on a rise in other countries, it is decreasing in the country which not only implies that there are plenty of work to do to reach a higher living donation rate, but also means that the potency of living donation in this country are huge and worth the efforts. For this purpose, a survey to explore the quality of life of living kidney donors in Malaysia had been conducted by using a shorter version of the Short Form 36 (SF-36), i.e., the SF-12 of health survey, which was performed in 80 respondents out of 170 contacted living kidney donors of the donation time periods of 1990 to 2012. Analyzed data show the following three major conclusions: Firstly, the qualities of lives of living kidney donors have been improved after organ donations. Secondly, the living capabilities of the living kidney donors did not decrease but were maintained indicating that living donations should be encouraged and promoted among the Malaysian populations, and these data can be used to educate people in the country to have better confidences and stronger potencies to kidney donations. Thirdly, the results suggest that the enhancements and set-up of government policies and donor specific registry systems is necessary for helping living kidney donors to receive supports from the society, and well control their social activities after organ donations. This research is strongly proposing a live donor kidney registry with policies to protect quality of life for living organ donor to be initiated and eventually implemented in Malaysia. This is urgently needed to protect living donors’ lives and to promote increased numbers of future living donors in this country. An open, simple and easy means to use living kidney donor registry with policies to protect the quality of life of living donors could be a rapid and effective solution to the current problematic kidney donation situations.